P‐79: Evaluation of Diffraction Induced Background Image Quality Degradation through Transparent OLED Display. Issue 1 (29th May 2019) - Cheng, Chi Jui; Huang, Tzu Chin; Lin, Wen Tsan; Hsieh, Cheng Chih; Chen, Peng Yu; Lu, Peter; Lin, Hoang Yan
Abstract : For current transparent OLED displays, a common observation is that the background image quality is worsened when viewed through the transparent display, due to diffractive effects of the periodic grating‐like structure of the display. The aim of this work, therefore, is to develop a method to quickly and accurately evaluate the influence on the background image caused by the transparent display, as a transfer function acting on the background image, to assist in further optimization of the display structure.